Penerapan Statistik Manajemen dalam Pengambilan Keputusan di Bidang Administrasi Pendidikan - Prihaten Maskhuliah; Sastya Nawangsari; Nirmaya Rumakat; Mohamad Salis Garamatan; Ardiyanto N. Tupong (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Decision-makers in educational administration face increasingly complex challenges along with the need for accountability, honesty, and quality education services. Based on the book